Day 1 Mon, May 06, 2019 2019
DOI: 10.4043/29557-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Findings of the PISA Joint Industry Project in the Design of Monopile Foundations for a North Sea Wind Farm

Abstract: Monopiles are the most common foundation type in the offshore wind industry. Their design is largely dependent on the ability to accurately model the soil-structure response of the foundation, with more refined modelling approaches enabling significant reductions in required embedment depth, fabrication cost and installation risk. The PISA joint industry project (JIP) has been completed in recent years with the objectives of developing a more refined soil-structure response modelling method compared to other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Comparison of the 3D mass soil and API‐RP springs‐supported models performed as part of the PISA project supports the findings of this study. Ratio of horizontal load at the top of the OWT structure to the pile head displacement (force/displacement) was reported to be 19.38 for the 3D mass soil model and 8.75 for the API‐RP model 5,17 . This represents a 121% increase in 3D mass soil model stiffness on the API‐RP spring‐supported model stiffness.…”
Section: Findings and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Comparison of the 3D mass soil and API‐RP springs‐supported models performed as part of the PISA project supports the findings of this study. Ratio of horizontal load at the top of the OWT structure to the pile head displacement (force/displacement) was reported to be 19.38 for the 3D mass soil model and 8.75 for the API‐RP model 5,17 . This represents a 121% increase in 3D mass soil model stiffness on the API‐RP spring‐supported model stiffness.…”
Section: Findings and Discussionmentioning
confidence: 98%
“…The springs supported models can still be applied in the design of OWT monopiles, but this would require significant deviation from current springs force–stiffness calculation and instead rely heavily on calibration using both the mass soil model and measured monitoring data to verify, investigate, and correct uncertainties in the design 19 . Engineering justification and benefit for undertaking the design and analysis using this method can be made on the grounds of reducing computational costs and improving efficiency considering the sheer number of modelling iterations, improvements, loading conditions, and combinations required for the complete structural design of OWT monopiles 17 …”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study formed part of the PISA Joint Industry Project described by Byrne et al (2017) and Zdravković et al (2020a) which included numerical analyses and lateral loading tests on instrumented monopiles, with diameters up to 2m, at the Cowden site, that were designed to improve design for monopiles driven to support large turbines at many North and Baltic Sea glacial till offshore windfarm sites, see Schroeder et al (2015Schroeder et al ( , 2020 or Manceau et al (2019). The laboratory research described herein aimed to resolve the significant mismatch noted by Zdravković et al (2020b) between stiffness trends found from triaxial undrained compression tests on Cowden till and those inferred from field and laboratory geophysical testing and observed in the PISA pile tests.…”
Section: Introductionmentioning
confidence: 99%